Sero-molecular epidemiology of hepatitis E virus in pigs and human contacts in Ghana - Richmond Yeboah; Augustina Angelina Sylverken; Michael Owusu; Philip El-Duah; Vitus Burimuah; Yaw Frimpong; Jones Lamptey; Isabella Eckerle; Benjamin Meyer; Christopher Antwi; Olivia Agbenyaga; Raphael Folitse; et al. (BMC, 2021)
Abstract Background Hepatitis E virus (HEV) is among the leading causes of viral hepatitis in most developing countries. Zoonotic acquisition of HEV genotype 3 from swine has come into focus more recently. Available studies on HEV in Ghana and other countries in the region do not provide enough information towards understanding the epidemiology of HEV in human and animal populations. Towards this end, we conducted a comparative cross-sectional study to determine the seroprevalence and risk factors associated with HEV exposure, both in swine and humans working on pig farms in typical local settings. The presence of viral RNA in human and swine samples was also evaluated, along with classification of viral sequences from HEV-positive samples. Methods Structured questionnaires soliciting information on pigs reared, as well as socio-demographic information including age, sex and educational background of humans was collected. A total of 10 ml and 5 ml of whole blood was collected from pigs and human participants respectively. ELISA and real-time RT-PCR were performed on the sera for the qualitative detection of IgG antibodies to hepatitis E virus and viral RNA, respectively. Results Five hundred and forty-four (544) human participants including 264 swine contacts and 280 swine non-contacts were enrolled in the study. Although the proportion of HEV IgG antibodies was higher in contact groups (114; 54.3%) than non-contact groups (96; 45.7%), a multivariate analysis did not show any significant difference. No HEV RNA was detected in human samples. Similarly, 720 pigs were sampled from 18 farms located in five regions in Ghana. Twenty-three (23) of the pigs (3.2, 95%CI = 2.0-4.8) were positive for HEV RNA by real-time RT-PCR testing. Sequences obtained from HEV-positive samples were found to share high sequence identities with each other and clustered with other genotype 3 viruses indicating the existence of circulating zoonotic genotype 3 viruses on farms. Although we did not find evidence of pig to human transmission of HEV genotype 3, the presence of this genotype in pigs shows the potential for possible zoonotic transmission in African farm settings and buttresses the importance of active surveillance for the infection among at risk populations.